2020
DOI: 10.1186/s12886-020-01515-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical results between trans-PRK and femtosecond LASIK for correction of high myopia

Abstract: Background: To compare the clinical outcomes of transepithelial photorefractive keratectomy (TPRK) with femtosecond laser-assisted in situ keratomileusis (FS-LASIK) for correction of high myopia. Methods: In this prospective, non-randomised, cohort study, 85 eyes of 46 patients treated with TPRK and 80 eyes of 42 patients treated with FS-LASIK were included. All eyes were highly myopic (spherical equivalent refraction <− 6.00 diopters). Both TPRK and FS-LASIK were performed by Schwind Amaris 750S excimer laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…Our case series resembled the other TransPRK cohorts in terms of preoperative myopia and postoperative UCVA and efficacy and safety indices. Our predictability index (96%) tended to be higher than those of the other TransPRK cohorts (59–87%), possibly because refraction stabilizes at 6–12 months; our study duration was 6 months whereas the studies that reported predictability had durations of 12 months [ 25 , 26 , 28 30 , 34 ]. Our low rate of clinically significant haze was also observed by six of the studies (0–1% of patients had Fantes grade ≥2 at the end of follow-up).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Our case series resembled the other TransPRK cohorts in terms of preoperative myopia and postoperative UCVA and efficacy and safety indices. Our predictability index (96%) tended to be higher than those of the other TransPRK cohorts (59–87%), possibly because refraction stabilizes at 6–12 months; our study duration was 6 months whereas the studies that reported predictability had durations of 12 months [ 25 , 26 , 28 30 , 34 ]. Our low rate of clinically significant haze was also observed by six of the studies (0–1% of patients had Fantes grade ≥2 at the end of follow-up).…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, Zhang et al . reported using cold balanced salt solution after laser ablation [ 25 ]. Two, non mutually exclusive, hypotheses can explain the lack of haze after TransPRK in high myopia without mitomycin-C. First, applying cooled physiological fluids before/after the procedure may reduce the increased corneal temperature caused by the thermal effect of excimer laser ablation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with our report. A recent study [ 20 ] followed up for 12 months to compare the changes of corneal HOAs between Trans-PRK and FS-LASIK for high myopia, and found that corneal HOAs and vertical coma in the Trans-PRK group were statistically significantly lower than those in the FS-LASIK group, while the horizontal coma and spherical aberration of the cornea were similar between the two groups. We believe that diopter difference may be the reason for the difference between the results of this study and those of theirs.…”
Section: Discussionmentioning
confidence: 99%
“…LASIK had a slightly better efficacy, predictability, and lower enhancement rate, 28 while haze was still a problem in PRK for myopia > 10 D. 21 Recent PRK outcomes have been excellent for high myopic (>6 D) correction compared to femtosecond laser-assisted LASIK (F-LASIK). 29,30 Moreover, PRK induced less HOA than F-LASIK. 30,31 Compared to our previous study on F-LASIK outcomes with the same excimer laser machine and treatment profile (WFO), the efficacy of PRK in this present study for both treatment groups are slightly better than those of F-LASIK.…”
Section: Discussionmentioning
confidence: 95%